Role and mechanism of a novel fusion gene RELCH-RET in driving malignant transformation of human bronchial epithelial cells: a preliminary study - ZHOU Xiaogang; ZHOU Xiaogang; HAO Xianglin; XIA Jiying (陆军军医大学学报)
‍Objective‍　‍To investigate the role and primary mechanism of a novel fusion gene RELCH-RET in driving the malignant transformation of normal human bronchial epithelial (HBE) cells. Methods‍　‍Based on retrospective clinical data from 456 non-small cell lung cancer (NSCLC) patients admitted in the Second Affiliated Hospital of Army Medical University from January 2019 to June 2022, a fusion gene, RELCH-RET, was identified as a research target. Three cell models were established: negative control (HBE VC, transfected with empty lentiviral vector), RET control (HBE RET, transfected with lentiviral overexpression vector of Flag-RET), and experimental group (HBE RELCH-RET, transfected with lentiviral overexpression vector of Flag-RELCH-RET). MTS assay and Transwell assay were used to detect cell proliferation and migratory and invasive abilities. In vivo tumorigenicity of the 3 cell models was assessed in 15 female non-obese diabetic/severe combined immunodeficiency (NOD/SCID) mice (SPF grade, 4 weeks old, weighing 15.1±0.4 g) via subcutaneous xenograft experiments, with 5 animals in each group. Western blotting was employed to detect the autophosphorylation of RET (Y905) and the phosphorylation of downstream signaling proteins ERK1/2, EGFR (Y845) and STAT3 (Y705). Dimerization and multimerization status of RELCH-RET were analyzed by chemical cross-linking (DTME treatment) in combination with Western blotting, with the reversibility being confirmed through de-cross-linking experiments. Results‍　‍There were 3 cases carrying RELCH-RET fusion gene screened out from the 469 NSCLC patients. Compared with the HBE VC and HBE RET groups, the HBE RELCH-RET group exhibited significantly enhanced cell proliferation (P<0.01), and acquired migratory and invasive abilities (P<0.01), while the control groups did not demonstrate the abilities. In the mouse xenograft tumor model, HBE cells stably expressing RELCH-RET developed significant tumor nodules (P<0.001), whereas the control groups (empty vector and wild-type RET) failed to exhibit detectable tumor growth. Western blotting revealed that RELCH-RET could induce the autophosphorylation of the RET tyrosine residue (Y905) and significantly up-regulate the phosphorylation levels of ERK1/2, EGFR (Y845), and STAT3 (Y705) proteins. Chemical cross-linking combined with Western blot analysis demonstrated that RELCH-RET formed a dimer (~170 kDa) in HBE cells, which is reversibly dissociated into monomers upon decross-linking treatment. Conclusion‍　‍The novel fusion gene RELCH-RET, promotes ligand-independent dimerization/oligomerization, thereby mediating RET autophosphorylation, subsequently activates the downstream typical RET signaling pathway and ultimately drives the malignant transformation of normal HBE cells.